Changes in brain connectivity and neurovascular dynamics during dexmedetomidine-induced loss of consciousness - Panagiotis Fotiadis; Andrew R. McKinstry-Wu; Sarah M. Weinstein; Philip A. Cook; Mark Elliott; Matthew Cieslak; Jeffrey T. Duda; Theodore D. Satterthwaite; Russell T. Shinohara; Alexander Proekt; Max B. Kelz; John A. Detre; et al. (Communications Biology)
Abstract Understanding the neurophysiological changes underlying conscious-unconscious transitions is a key goal in neuroscience. Using magnetic resonance neuroimaging, we investigate the network connectivity and neurovascular changes occurring as the human brain transitions from wakefulness to dexmedetomidine-induced hypnosis, and recovery. Hypnosis led to widespread decreases in functional connectivity strength and increased structure-function coupling, indicating functional patterns more constrained by the underlying anatomical connectivity. As individuals began to regain consciousness, both connectivity markers returned towards awake levels, with particularly prominent coupling changes across the cerebellum. Neurovascular dynamics were disrupted during hypnosis as well: cerebral blood flow decreased globally—most notably in the brainstem, thalamus, and cerebellum—and continued decreasing even as recovery commenced, except within the cerebellum. Notably, regions with higher functional connectivity strength during wakefulness exhibited greater blood flow reductions during hypnosis. Hypnosis also heightened the amplitude of low-frequency fluctuations in the hemodynamic signal, especially in visual and somatomotor regions. Critically, individuals who regained consciousness faster displayed higher baseline levels of both neurovascular, but not connectivity, markers. Together, these results reveal that the induction of, and emergence from, dexmedetomidine-induced unconsciousness involve widespread, coordinated changes in brain connectivity and neurovascular function; across our findings, we also highlight the recurrent role of cerebellum in conscious-unconscious transitions.